The Effectiveness of Native Advertising on Purchase Intention: A Study Using the Elaboration Likelihood Model (ELM) Persuasion Theory - Feni Khairifa; Safrin Safrin (Lembaga Riset Ilmiah, 2026)
Native advertising is an advertising format designed to resemble organic content, enabling marketers to reduce consumer resistance to conventional advertising. This study examines the effect of native advertising on purchase intention based on the Elaboration Likelihood Model (ELM), with attitude toward advertising serving as a mediating variable and consumer involvement as a moderating variable. A quantitative associative approach was employed through a survey of 200 social media users and online news readers in Medan City, Indonesia, who had previously been exposed to native advertising and were selected using purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings indicate that argument quality, advertisement attractiveness, and source credibility positively influence attitude toward advertising, which subsequently enhances purchase intention. Multigroup analysis confirms that the central route is more influential among highly involved consumers, whereas the peripheral route has a stronger effect on consumers with low involvement. These findings support the applicability of ELM in explaining the effectiveness of native advertising and provide practical implications for developing adaptive digital marketing strategies. The novelty of this study lies in its explicit integration of the ELM dual-route mechanism with involvement-based multigroup analysis in the native advertising context, an approach rarely applied in Indonesian digital marketing research, thereby contributing both theoretically by extending ELM to a contemporary persuasion format and practically by providing segmentation guidance for digital marketers.